Diet, Physical Activity, and Screen Time to Sleep Better: Multiple Mediation Analysis of Lifestyle Factors in School-Aged Children with and without Attention Deficit Hyperactivity Disorder. Issue 13 (November 2021) - Hong, George C.C.; Conduit, Russell; Wong, Jason; Di Benedetto, Mirella; Lee, Eunro
Objective: This study examined the mediation roles of multiple lifestyle factors in school-aged children. Structural equation modeling (SEM) tested how lifestyle factors play mechanism roles one another in the impact of ADHD to seek theoretical and intervention insights. Method: An online survey assessed children's lifestyle factors including diet, physical activity, screen time, sleep difficulties, and having ADHD diagnosis. A multi-country sample from English speaking nations included 309 caregivers. Multiple regression and SEM were planned to identify significant correlates and mediators of ADHD in explaining lifestyle differences. Results: Preliminary multiple regression showed only sleep quality was significantly different between children with and without ADHD. Significant triple mediation effects suggested diet, physical activity, and screen time mediated the ADHD impact on sleep quality. Conclusion: Researchers and practitioners may incorporate the findings to develop intervention models for children with ADHD attending to the mediational roles of lifestyle factors to improve sleep quality.